ANALISIS FUNGSI BPD (BADAN PERMUSYAWARATAN DESA): STUDI PADA BPD DI DESA PENDARUNGAN KECAMATAN KABAT KABUPATEN BANYUWANGI - Ulfa, Helda Maria; Permatasari, Safrieta Jatu; Hentika, Niko Pahlevi (Jawa Dwipa, 2024)
This study aims to analyze the implementation of the functions of the Village Representative Body (BPD) in Pendarungan Village, Kabat District, Banyuwangi Regency, as well as the factors that drive and hinder its performance. According to Banyuwangi Regency Regional Regulation No. 2 of 2017, the BPD has three main functions: discussing and agreeing on village regulations, accommodating and channeling community aspirations, and overseeing the performance of the village head. This research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results show that the implementation of the BPD's functions in Pendarungan Village has not been fully optimal. The function of discussing village regulations is not effective due to the lack of initiative and attendance of BPD members. However, the function of channeling community aspirations works fairly well, although not all aspirations are immediately followed up. The oversight of the village head's performance is also hindered by delays in reporting from the village head. Factors that support the BPD's performance include adequate facilities and sufficient budget, while the main obstacles are delays in reporting on development and the lack of cohesion among BPD members. This study recommends improving coordination, increasing the initiative of BPD members, and involving the BPD in every stage of village development planning to ensure that the BPD's functions can be optimally implemented, in accordance with the expectations of the community and applicable regulations.